DEVELOPMENT OF WEBSITE-BASED ART-CARE GUIDANCE AND COUNSELING MEDIA TO PREVENT SELF-INJURY BEHAVIOR OF JUNIOR HIGH SCHOOL STUDENTS - Annisa Maharani Masrurah; Farida Aryani; Abdullah Pandang (JURNAL NALAR PENDIDIKAN, 2026)
This research aims to prevent self-harm behavior among students in the city of Makassar through a web-based guidance and counseling medium called Art-Care. This study discusses the following problem statements: (1) what is the need for web-based Art-Care guidance and counseling media to prevent self-harm among students in Makassar; (2) how the process of developing Art-Care's web-based guidance and counseling media; (3) how effective the media is in preventing self-harm among students in Makassar; and (4) how practical the media is based on user evaluation. The research method used is a modified version of the Borg and Gall development model, which consists of seven stages: preliminary study, initial product design, initial product development, expert validation, product revision, limited trial, and final revision. Data collection techniques include needs assessment questionnaires, expert validation sheets, and instruments to evaluate the practicality and effectiveness of the media. The results of the study show that Art-Care media is needed by students and school counselors in preventing self-harm. Expert validation assesses that the media is very feasible. Limited field trials and tests show that media has a high level of practicality and effectiveness in helping students recognize and manage self-harm tendencies. Therefore, Art-Care media is considered suitable as an alternative to web-based guidance and counseling services to prevent self-harm in junior high school students in Makassar.